PENGARUH PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) MELALUI METODE INKUIRI PADA SISWA SEKOLAH DASAR - Lailatul Azkia; Sastra Wijaya; Dhea Amaliya; Nadilah (STKIP Subang, 2024)
This study explores the influence of Social Science (IPS) learning through inquiry methods on elementary school students. In education, an important role is played to shape the character and knowledge of students, preparing them for future challenges. Innovative approaches to learning are key to creating an environment that supports better understanding, increasing students' interest and learning activities, especially in social studies subjects. This study uses the literature study method to analyze previous research journals related to the influence of social studies learning through inquiry methods. The results of the analysis show that the inquiry method is effective in improving students' understanding of concepts and skills, with the use of media considered important to make learning more interesting. In the implementation of inquiry methods in social studies teaching, the use of media helps overcome student boredom, increase learning motivation, and explain the material better. In addition, the online-based Inquiry learning model also contributes positively to students' learning outcomes and argument skills. The relationship between learning methods and student learning motivation is a key aspect, where students with high motivation tend to be more active and like to discuss, according to the characteristics of the inquiry method. Conversely, students with low motivation tend to be hesitant and lack confidence, hampering their ability in social studies practice. The development of social inquiry strategies includes social aspects in the classroom, the formation of hypothesis formulations, and testing hypotheses with facts. The advantage of the inquiry method lies in the development of cognitive, affective, and psychomotor aspects in a balanced manner, in accordance with the development of modern learning psychology.